MISCELLANEOUS BOTANICAL NOTES XXVI - STEENIS, C. G. G. J. VAN; Veldkamp, J. F. (REINWARDTIA, 1982)
Description of the pod of the type tree of Ormosia incerta Koord. (reduced to 0. psnangensis Ridl.) from Java. Reduction of the genus Trifidacanthus Merr. (Legum.) to Desmodium; one new combination necessary. The genus Platyspermation Guillaumin described from New Caledonia in Myrtaeeae, suggested to belong to Saxifragaceae-Escallonioidsae. Juncus bufonius L. recorded as introduced on Mt Kinabalu. Two Fimbristylis species recorded new for the Northern Territory, Australia; Oreobolus kukenthalii Steen. recorded from Mt Muln, Sarawak.